Efeito do metotrexato e do bisfosfonato alendronato em modelo do carcinossarcoma 256 de Walker na mandíbula de ratos - Alves, Ana Paula Negreiros Nunes (2005)
The pathologic resorption of alveolar bone seen in a wide variety of malignant neoplasms is often severe and fatal, leading to early microfractures. Bone invasion occurs as a consequence of subcortical progression of tumor through dental alveoli. We investigated the effect of the Metotrexate (MTX) and the Bisphosphosnate Alendronate (ALD) on experimental model of Walker 256 carcinossarcoma developed in the oral cavity of rats. Walker 256 carcinossarcoma cell suspension containing 106 cell/mL was implanted in the alveoli of first and second molars. The animals were divided and treated with saline, MTX, ALD, and MTX plus ALD. The animals were observed during all the treatment to determine the body weigth and life survival. Later, the animals were sacrificed, the tumors were measured and their mandibles removed to radiographic and histologic analysis. In the control group, the radiographic image demonstrated radioluscencie with poorly defined borders, and the microscopic examination revealed tumor infiltration into the peripheral and central regions of bone. Areas of necrosis were commonly seen. In the treaties groups with ALD, associated or not with MTX, the radiographic analysis revealed tumor-induced osteolyse circumscribed and variety degrees of radiotransparence; histologically, bony trabeculae were preserved and producing osteoid among malignant cells. The metotrexate induced significant antitumoral activity and the treaties animals showed a survival increase. Thus, the combination of metotrexate with alendronate is more successful, than single agents, in the control of the growth of neplastics cells, and its stimulation of reactive new bone. Therefore, it constitutes a new treatment to malignant lesions of maxillares with osteolysis.